2018
DOI: 10.1038/s41598-018-20625-5
|View full text |Cite
|
Sign up to set email alerts
|

A computationally driven analysis of the polyphenol-protein interactome

Abstract: Polyphenol-rich foods are part of many nutritional interventions aimed at improving health and preventing cardiometabolic diseases (CMDs). Polyphenols have oxidative, inflammatory, and/or metabolic effects. Research into the chemistry and biology of polyphenol bioactives is prolific but knowledge of their molecular interactions with proteins is limited. We mined public data to (i) identify proteins that interact with or metabolize polyphenols, (ii) mapped these proteins to pathways and networks, and (iii) anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 58 publications
(69 reference statements)
2
60
0
Order By: Relevance
“…Like E2, D, D4S, and Eq trigger ERαS118 phosphorylation, even if only E2 reduces the receptor levels, an important mechanism for E2-induced cancer cell proliferation [34]. Moreover, ERα is necessary for D and its metabolites to regulate NGB levels, confirming that D and its metabolites could bind to and activate ERα, as already reported [3]. However, downstream of ERα activation, D and its metabolites trigger divergent signal pathways.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Like E2, D, D4S, and Eq trigger ERαS118 phosphorylation, even if only E2 reduces the receptor levels, an important mechanism for E2-induced cancer cell proliferation [34]. Moreover, ERα is necessary for D and its metabolites to regulate NGB levels, confirming that D and its metabolites could bind to and activate ERα, as already reported [3]. However, downstream of ERα activation, D and its metabolites trigger divergent signal pathways.…”
Section: Discussionsupporting
confidence: 66%
“…Due to their molecular structure and size, some of these molecules, including lignans, flavonoids, and stilbenes, have a chemical structure that resembles that of human estrogens, in particular to 17-β-estradiol (E2) [2]. Among other, isoflavones, a class of flavonoids ranked among the most estrogenic compounds, bind to estrogen receptor subtypes (i.e., ERα and ERβ) [3,4] exerting estrogenic and/or antiestrogenic effects [1]. For isoflavones, the key to their bioactivity in human and animals seems to rely on their (anti)estrogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicated that DAI can regulate the hypothalamic-pituitary-gonad axis of the endocrine system by competitively binding with estrogen receptors [17]. At the present study, we observed that daidzein supplementation signi cantly increased the levels of estrogen and tended to increase the activity of progesterone in the amniotic uid, which is consistent with a previous study that daidzein could improve estrogen and progesterone levels of female rat during pregnancy [19].…”
Section: Discussionsupporting
confidence: 92%
“…Daidzein (7,4′-dihydroxyiso avone, DAI) is a class of non-steroidal polyphenolic secondary metabolites, which has attracted considerable research interests because of their antioxidant, anti-in ammatory, and differentiation-inducing abilities [14][15][16]. Importantly, it can directly bind to estrogen receptor subtypes (i.e., ERα and ERβ) to exert estrogenic and/or antiestrogenic effects [17]. Extensive studies have focused on the role of daidzein on animal growth and health [18].…”
mentioning
confidence: 99%
“…The large list of polyphenols identified from FooDB is larger than the list of 1,395 polyphenols identified and used in the recent work of Lacroix et al . ( Lacroix et al ., 2018 ) that was retrieved from Phenol-Explorer and the Dictionary of Natural Products. Indeed, the list of 3,228 polyphenolic compound made available in this work can be used to augment the already extensive polyphenol-protein interactome work of Lacroix et al .…”
Section: Resultsmentioning
confidence: 99%